2017
DOI: 10.1016/j.canep.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal trends of diagnosis of childhood malignant diseases and viral prevalence in South Korea

Abstract: This study tentatively suggests that the diagnosis of childhood malignancy follows a seasonal trend in Korea, and has a possible correlation with viral prevalence in several diseases. Further long-term analysis of epidemiological data is needed to explore possible causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The potential association of season of birth with the risk of childhood cancers has been previously investigated in an attempt to shed light in the complex etiology of childhood carcinogenesis . Certain researchers have suggested a seasonal variation in several types of cancer, such as leukemia, non‐Hodgkin lymphoma, neuroblastoma and CNS tumors, whereas other studies have not confirmed similar associations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential association of season of birth with the risk of childhood cancers has been previously investigated in an attempt to shed light in the complex etiology of childhood carcinogenesis . Certain researchers have suggested a seasonal variation in several types of cancer, such as leukemia, non‐Hodgkin lymphoma, neuroblastoma and CNS tumors, whereas other studies have not confirmed similar associations .…”
Section: Discussionmentioning
confidence: 99%
“…The potential association of season of birth with the risk of childhood cancers has been previously investigated in an attempt to shed light in the complex etiology of childhood carcinogenesis. [29][30][31] Certain researchers have suggested a seasonal variation in several types of cancer, such as leukemia, non-Hodgkin lymphoma, neuroblastoma and CNS tumors, 21,29,31 whereas other studies have not confirmed similar associations. 30 Consistently with our findings, a recent systematic review of the literature (n = 7 studies) 22 showed a potential peak of births in autumn and winter months among children and adults diagnosed with CNS tumors; however, the results were based on studies suffering lack of power, not reporting the size of effect, neither were the findings confined to specific histological subtypes.…”
Section: Previous Literaturementioning
confidence: 98%
“…Применительно к роли ЭФ в возникновении ЗН у детей в настоящее время известно, что 5-10 % данной патологии связаны с ионизирующей радиацией [22]. Есть данные о корреляции частоты острого лимфобластного лейкоза, нейробластомы и лимфогранулематоза с сезонными колебаниями распространенности вирусных инфекций [26]. Сол-нечное ультрафиолетовое излучение снижает риск развития острого лимфобластного лейкоза, гепатобластомы и неходжкинской лимфомы [21], однако увеличивает риск возникновения ретинобластомы [18].…”
Section: оригинальные статьиunclassified
“…The association of season of birth with the diagnosis of pediatric cancer has been previously investigated [276,411,412] in an attempt to shed light in the complex etiology of childhood carcinogenesis. Certain researchers have suggested a seasonal variation for some types of cancer, such as leukemia, non-Hodgkin lymphoma, neuroblastoma and CNS tumors [276,288,412], whereas other studies have not confirmed similar associations [411].…”
mentioning
confidence: 99%
“…The association of season of birth with the diagnosis of pediatric cancer has been previously investigated [276,411,412] in an attempt to shed light in the complex etiology of childhood carcinogenesis. Certain researchers have suggested a seasonal variation for some types of cancer, such as leukemia, non-Hodgkin lymphoma, neuroblastoma and CNS tumors [276,288,412], whereas other studies have not confirmed similar associations [411]. Consistently with our findings, a recent systematic review of the literature (N=7 studies) [291] showed a potential peak of births among children and adults with CNS tumors in fall and winter months; however, the results were in general based on studies suffering lack of power, which did not report the size of effect, neither were the findings confined to specific histological subtypes.…”
mentioning
confidence: 99%